Color Enrichment Solids of Spectrally Pure Colloidal Quantum Wells for Wide Color Span in Displays - Erdem, Talha; Soran-Erdem, Zeliha; Isik, Furkan; Shabani, Farzan; Yazici, Ahmet Faruk; Mutlugun, Evren; Demir, Hilmi Volkan (Wiley-VCH Verlag GmbH, 2022)
Colloidal quantum wells (CQWs) are excellent candidates for lighting and display applications owing to their narrow emission linewidths (<30 nm). However, realizing their efficient and stable light-emitting solids remains a challenge. To address this problem, stable, efficient solids of CQWs incorporated into crystal matrices are shown. Green-emitting CdSe/CdS core/crown and red-emitting CdSe/CdS core/shell CQWs wrapped into these crystal solids are employed as proof-of-concept demonstrations of light-emitting diode (LED) integration targeting a wide color span in display backlighting. The quantum yield of the green- and red-emitting CQW-containing solids of sucrose reach approximate to 20% and approximate to 55%, respectively, while emission linewidths and peak wavelengths remain almost unaltered. Furthermore, sucrose matrix preserves approximate to 70% and approximate to 45% of the initial emission intensity of the green- and red-emitting CQWs after >60 h, respectively, which is approximate to 4x and approximate to 2x better than the drop-casted CQW films and reference (KCl) host. Color-converting LEDs of these green- and red-emitting CQWs in sucrose possess luminous efficiencies 122 and 189 lm W-elect(-1), respectively. With the liquid crystal display filters, this becomes 39 and 86 lm W-elect(-1), respectively, providing with a color gamut 25% broader than the National Television Standards Committee standard. These results prove that CQW solids enable efficient and stable color converters for display and lighting applications.
Erdem, Talha/0000-0003-3905-376X; Mutlugun, Evren/0000-0003-3715-5594; Soran Erdem, Zeliha/0000-0001-7607-9286; Gaponik, Nikolai/0000-0002-8827-2881; Shabani, Farzan/0000-0003-2174-5960; Demir, Hilmi Volkan/0000-0003-1793-112X; Isik, Furkan/0000-0001-5881-5438;
Keywords: Colloidal Quantum Wells; Displays; Emission Stability; Lighting; Nanoplatelets